The relationship between emotional and functional choices of club athletes in the context of employer brand and organizational attractiveness - Tuba Turan Heveslı (Selcuk University, 2016)
Being a part of an organization is one of the most important targets for every single individual. For this purpose, individual works and develops himself/herself. On the other hand, to provide its own prestige, choosing suitable and quality individuals is an important move. These mutual relations are explained with interest on an organization for employees or candidates. Values and image of an organization cause attractiveness for individuals that they want to be a part of it. This situation, which is called "organizational attractiveness", is defined with a brand, a name or attention on a specific symbol for individuals. In this process, emotional choices come forward and the expectations of individuals from organization are observed. Attention on a specific organization comes out with emotional factors mostly. At the same time, while individuals feel themselves as a part of an organization, they think about the benefits of that organization and they make their choices in this direction. In the sport world, the same thing is valid for the football players; the football players find the clubs that they feel themselves closer and support it as attractive and they think about benefits in the sportive image and financial mean as a part of that club. This study, in the basis of a survey, evaluates the attitudes of football players with the relations between organizational attractiveness, emotional and functional benefit. The outputs of study and survey unroll which factors important are for the choices of football player to play in a club.